Wellness X-16, UiTM Sarawak / Muhammad Zulhairie Zulazizi and Luqmanul Hazim Muhammad Faiz - Zulazizi, Muhammad Zulhairie; Muhammad Faiz, Luqmanul Hazim (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Many students today believe that sports can only be done by jogging, playing games using sports equipment, and going to the gym. However, undergraduate students in semester 3 from the Faculty of Sports Science and Recreation at UiTM Sarawak Samarahan Campus made the effort by organizing the event "WellnessX16," which took place on January 5th, 2023 at UiTM Kota Samarahan 1. Wellness X-16's major goal is to fulfil the criteria of the SPS500 (Applied Physical Fitness and Wellness) curriculum by promoting physical and mental health to individuals and communities of all races, religions, and backgrounds. Besides helping the students meet the requirements of the SPS500 (Applied Physical Fitness and Wellness) subject syllabus, this programme also encouraged the students to participate in sports and recreational activities, apply elements of a healthy lifestyle to the community, and stimulate their minds to be active, productive, innovative, and motivated. Furthermore, the fostering of friendship among the participants helps to establish an atmosphere of peace, goodwill, and thoughtfulness. Finally, this event draws one closer to the people around them and encourages healthy interaction to foster strong social interactions. There was a group workout activity hosted at the Jubilee Hall at the UiTM Samarahan Campus. This activity was supplemented by six other types of group exercises: Zumba, Kickboxing, Hip Hop Aerobics, Pilates, Strong Zumba, and Qi Gong. Each workout category was led by two persons. Each category was accompanied by two songs. More than 400 students, teachers, and staff from the UiTM Sarawak Samarahan campus attended this event.